HIBRIDITAS GERAK DAN BUNYI: TRANSFORMASI METODOLOGI PENGKARYAAN TARI KONTEMPORER FLS3N BERBASIS DIGITAL AUDIO WORKSTATION - Vereki Martiano; Intania Ananada Jonisa; Susandra Jaya (Greget: Jurnal Kreativitas dan Studi Tari, 2026)
This study aims to comprehensively analyze the methodological transformation in creating contemporary dance by utilizing Digital Audio Workstation (DAW) Studio One 6 in the FLS3N competition, focusing on the work "Ratapan Bumi". The central problem highlights how digital technology functions not merely as a recording device, but rather as an integrated methodological environment bridging kinetic hybridity (Riau Malay Silat movements) and sonic spectrums (traditional-electronic instruments). Employing a qualitative approach with an interpretive case study design, empirical data were gathered through in-depth interviews with Composer Vic Art, systematic observation of the DAW project workflow, and contextual choreography document analysis. The results establish three digital methodology pillars with a prioritized emphasis on choreographic reconstruction and digital audio integration: (1) Converting the ecological narrative of Riau's forest crisis into a structured arrangement timeline using markers, (2) Generating timbral hybridity via third-party VST layering (Native Instruments Kontakt) to blend authentic traditional Malay resonances with software synthesis, and (3) Optimizing Automation Tracks as a direct translation tool for kinetic silat energy demanding high synchronization accuracy. This study confirms that DAW integration within contemporary dance choreography fosters an interdisciplinary paradigm where physical movement structures and digital sound design inherently co-construct one another.